Improving The Ability To Recognize Number Symbols Through The Manipulative Numbers Dice Game In Children Ages 3 – 4 Years : Peningkatan Kemampuan Mengenal Lambang Bilangan Melalui Permainan Manipulatif Dadu Angka Pada Anak Usia 3 – 4 Tahun - Candu Gayuk Sheril; Choirun Nisak Aulina (Universitas Muhammadiyah Sidoarjo, 2021)
Based on the observations of researchers at PG Mutiara Cita Hati Sidoarjo, they found a problem in PG TK Mutiara Cita Hati Sidoarjo, namely the difficulty of children aged 3-4 years in knowing numbers. Whereas out of 16 children aged 3 - 4 years (PG), there are 10 children who do not know numbers well. The process of counting, namely adjusting between what is spoken and the number / results of the objects collected and counted is still not correct. This situation occurs because the learning is not in accordance with the learning theory. To be able to solve the problems listed above, the researchers made a game that can improve children's ability to recognize the symbol of numbers. Through this game, it can make it easier for children to understand and absorb lessons because the atmosphere is fun. In this study, it can be concluded that the application of the numerical dice manipulative game can improve the ability to recognize number symbols. This is indicated by an increase in the ability to count concepts in each cycle. Before the action and pre-cycle was 33.33%, 60% first cycle and 93.33% cycle II. In the stage of recognizing the symbol of numbers, all stages are carried out using the application of the number dice manipulative game